Arterial spin labelling MRI for detecting pseudocapsule defects and predicting renal capsule invasion in renal cell carcinoma. Issue 11 (November 2017) - Zhang, H.; Wu, Y.; Xue, W.; Zuo, P.; Oesingmann, N.; Gan, Q.; Huang, Z.; Wu, M.; Hu, F.; Kuang, M.; Song, B.
Abstract : Aim: To evaluate prospectively the performance of combining morphological and arterial spin labelling (ASL) magnetic resonance imaging (MRI) for detecting pseudocapsule defects in renal cell carcinoma (RCC), and to predict renal capsule invasion confirmed histopathologically. Materials and methods: Twenty consecutive patients with suspicious renal tumours underwent MRI. Renal ASL imaging was performed and renal blood flow was measured quantitatively. The diagnostic performance of T2-weighted images alone, and a combination of T2-weighted and ASL images for predicting renal capsule invasion were assessed. Results: Twenty renal lesions were evaluated in 20 patients. All lesions were clear cell RCCs (ccRCCs) confirmed at post-surgical histopathology. Fifteen ccRCCs showed pseudocapsule defects on T2-weighted images, of which 12 cases showed existing blood flow in defect areas on perfusion images. To predict renal capsule invasion, the sensitivity, specificity, positive predictive value, and negative predictive value were 100%, 71.4%, 86.7%, 100%, respectively, for T2-weighted images alone, and 92.3%, 100%, 100%, 87.5%, respectively, for the combination of T2-weighted and ASL images. Conclusion: ASL images can reflect the perfusion of pseudocapsule defects and as such, the combination of T2-weighted and ASL images produces promising diagnostic accuracy for predicting renal capsule invasion. Highlights: Arterial spin labeling imaging can reflect perfusion of pseudocapsule defects. Prospective study showed combining ASL and T2-weighted images provided greater specificity and positive predictive value. Management of renal cell carcinomas becomes more accurate.